PENGARUH PERSEPSI KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KEPUASAN KERJA DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SMA NEGERI 3 DENPASAR - Adipurwa, A A Gd Kasunu; Riana, I Gede (E-Jurnal Manajemen; Vol 4 No 3 (2015), 2015)
This study aimed to determine the effect of transformational leadership on job satisfaction and Organizational Citizenship Behavior (OCB) at the teacher in SMA3 Negeri Denpasar. Data collection techniques used in this study is a sampling saturated because all members of the population used as a respondent. The number of samples in this study were all full-time teacher who has the status of civil servants (PNS) as many as 46 teachers. Data analysis techniques used in the study is the technique of path analysis. Based on the analysis found that transformational leadership and job satisfaction positive and significant impacton Organizational Citizenship Behavior. Transformational leadership and significant positive effecton job satisfaction.
Keywords: Transformational Leadership, Job Satisfaction, Organizational Citizenship Behavior (OCB).